Determination of content of dechlorane plus flame retardant in rubber products by solvent precipitation and gas chromatography-micro cell electron capture method - YU Jian-long, HUO Wei-jiang, PENG Zhi-keng, LIU Zhi-wen, LI Quan-zhong (Hecheng xiangjiao gongye)
The content of dechlorane plus (DP) flame retardant in rubber products was detected by solvent precipitation and gas chromatography-micro cell electron capture method. The extraction efficiency of DP from three rubber samples was investigated using dichloromethane, acetone, tetrahydrofuran, and ethyl acetate. The results showed that tetrahydrofuran had better solubility in styrene-butadiene rubber, silicone rubber, and natural rubber, as well as better extraction effect on DP. The separation of DP was carried out using capillary chromatography columns with different polarities of 100% dimethyl polysiloxane, (5%-phenyl)-methyl polysiloxane, and polyethylene glycol. The results showed that the (5%-phenyl)-methyl polysiloxane column had good separation efficiency and high sensitivity for the cis- and trans-isomers of DP. By adding acetonitrile for solvent precipitation of polymer molecules in the extraction solution, the results showed that the signal-to-noise ratio of the spectrum and precision of the experiment were improved. DP showed a good linear relationship with the chromatographic peak area within the concentration range of 50-2 000 μg/L, with a detection limit of 50 μg/L. The spiked recovery rate of DP in blank matrix was 85.7%-102.0%, with a relative standard deviation range of 2.9%-4.8%. This method was accurate, efficient, and suitable for the analysis and detection of flame retardant DP in rubber products.